Options for using solid oxide fuel cell technology in complex integrated biomass gasification cogeneration plants. (March 2019) - Kalina, Jacek
Abstract: The aim of this paper is to draw readers' attention to potential new technological solutions for effective utilisation of dispersed biomass resources in distributed community-scale applications. In the paper conceptual system, that consists of allothermal wood gasifier, solid oxide fuel cell (SOFC), internal combustion piston engine (ICE) and Organic Rankine Cycle (ORC) for waste heat recovery, is proposed. Configuration of such systems is nowadays possible due to availability individual small-scale energy conversion technologies that can be integrated into complex structures. In the studied case the anode exhaust gas of the syngas fired SOFC module, that still contains combustible gases, is considered a secondary fuel for a bottoming ICE. The ORC cycle module is driven by the heat recovered from process gas coolers as well as from SOFC cathode and ICE exhaust gases. The system has been theoretically evaluated in terms of energy conversion efficiency and profitability using thermodynamic and economic analysis. Relevant robust mathematical models of key components have been developed. Through the modelling the most important performance parameters are addressed. Electric power of the sample system is below 1 MW what makes it suitable for utilisation of locally available biomass. Simulations revealed potentially high value of the net biomass energy to electricity conversion efficiency of 37%–40% depending on the ORC cycle configuration. Financial analysis revealed positive values of profitability indices at current level of market prices. The results are compared with a real biomass-fired ORC cogeneration project. The system also addresses issues related to external effects of the project, such as global emission reduction and primary energy savings. Highlights: Integrated gasification cogeneration plant of complex structure is proposed. Internal combustion gas engine is proposed as bottoming unit for solid oxide fuel cell. Evaluation of the concept is performed using mathematical modelling approach. Technical analysis reveals substantial efficiency gains, fuel savings and emission reduction. System profitability is estimated under current market and policy conditions.